COMPARATIVE ANALYSIS OF USING ENDOPROSTHETIC MESH IN THE TREATMENT OF UMBILICAL HERNIA IN CALVES (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This study investigates effective surgical approaches for treating umbilical hernia in calves raised in household conditions across the Republic of Karakalpakstan. Eight male calves participated in the experiment. Traditional open herniorrhaphy and mesh-reinforced hernioplasty techniques were applied. Postoperative outcomes, complication rates, and healing times were evaluated. Findings showed that mesh implantation demonstrated higher clinical effectiveness and safety in managing umbilical hernias in calves.